The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s13073-021-00920-z
|View full text |Cite
|
Sign up to set email alerts
|

Systems pharmacogenomics identifies novel targets and clinically actionable therapeutics for medulloblastoma

Abstract: Background Medulloblastoma (MB) is the most common malignant paediatric brain tumour and a leading cause of cancer-related mortality and morbidity. Existing treatment protocols are aggressive in nature resulting in significant neurological, intellectual and physical disabilities for the children undergoing treatment. Thus, there is an urgent need for improved, targeted therapies that minimize these harmful side effects. Methods We identified candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
3
1
Order By: Relevance
“…Moreover, the same study found that longer-lived cell lineages have an active X chromosome with a longer telomere than the inactive X, indicating that telomere maintenance alleles on the X chromosome impact survival. It was also suggested that the male Y chromosome is less protected and more prone to telomere shortening, but the chromosome-dependent telomere shortening is under debate (Genovesi et al 2021). The results of the current study could not demonstrate that in the given population females have longer telomeres than males.…”
Section: Discussioncontrasting
confidence: 85%
“…Moreover, the same study found that longer-lived cell lineages have an active X chromosome with a longer telomere than the inactive X, indicating that telomere maintenance alleles on the X chromosome impact survival. It was also suggested that the male Y chromosome is less protected and more prone to telomere shortening, but the chromosome-dependent telomere shortening is under debate (Genovesi et al 2021). The results of the current study could not demonstrate that in the given population females have longer telomeres than males.…”
Section: Discussioncontrasting
confidence: 85%
“…Moreover, the same study found that longer lived cell lineages have an active X chromosome with longer telomere than the inactive X, indicating that telomere maintenance alleles on X chromosome impact survival. It was also suggested that in male Y chromosome is less protected and more prone to telomere shortening, but the chromosome dependent telomere shortening is under debate (Genovesi et al 2021). The results of the current study could not demonstrate that at the given population females have longer telomere than males.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia and obesity share pathological factors, including aging, changes in BC, inflammation, and hormones ( 27 ). The aging process carries a low metabolic rate and metabolic adaptations, including adaptive thermogenesis and changes in oxidative capacity; this process favors the development and onset of SO ( 28 ). Changes in BC related to age are the main risk factor for SO.…”
Section: Methodsmentioning
confidence: 99%